Axillary lymph nodes in breast cancer cases - Jarkman, Sofia; Lindvall, Martin; Hedlund, Joel; Treanor, Darren; Lundstrom, Claes; Van Der Laak, Jeroen (AIDA Data Hub, 2019)
Whole slide imaging of 396 full cases of axillary lymph nodes in breast cancer cases. Included are both sentinel node surgery and axillary resections pre, peri or post breast cancer surgery or treatment. Sentinel node cases are cut in three levels (stained with HE) and one additional slide immunohistochemically stained with CKAE1/AE3. The number of sentinel node cases with complete immunohistochemical staining is 321. The axillary resections are cut with one cut level as default. No frozen sections included. The cases are anonymised and exported from the digital archive at the Department of Clinical Pathology in Linköping, Region Östergötland. Included are both positive and negative cases.
Keywords: Pathology; Whole slide imaging; Breast; Lymph nodes; Cancer; Sentinel nodes; Immunohistochemical staining; cytokeratin; CKAE1/AE3; Medical and Health Sciences; Medicin och hälsovetenskap; Cancer and Oncology; Cancer och onkologi